Odpowiedzi

2010-04-09T17:18:47+02:00
A) 0,25(x+8y)-(0,5x+15)(1+0,5y)=
=0,25x+2y-(0,5x+0,25xy+15+7,5y)=
=0,25x+2y-0,5x-0,25xy-15-7,5y=
=-0,25x-5,5y-0,25xy-22
b) -2(x-y) + 8(4x-1)(1-y)=
=-2x+2y+8(4x-4xy-1+y)=
=-2x+2y+32x-32xy-8-y=
=30x+y-32xy-8
c) 5x(2-x)= -4x(3+x) - x(do kwadratu) +44
10x-5x2(do kwadratu)=-12x-4x2(kwadrat)-x+44
10x-5x2=-13x-4x2+44
23x-x2=44
d)3x(-2+x) + 3x(do kwadratu) = 6x(1+x) +15
-6x+3x2+3x2=6x+6x2+15
-6x+6x2=6x+6x2+15
-12x=15
Najlepsza Odpowiedź!
2010-04-09T17:23:31+02:00
A) 0,25(x+8y)-(0,5x+15)(1+0,5y)
0,25x+2y-(0,5x-0,25xy+15+7,5)
0,25x+2y-0,5x+0,25xy-15+7,5
-0,25x+2y+6,5+0,25xy

b) -2(x-y) + 8(4x-1)(1-y)
-2x+2y+8(4x-4xy-1-y)
-2x+2y+32x-32xy-8-8y
30x-6y-32xy-8y

c) 5x(2-x)= -4x(3+x) - x(do kwadratu) +44
10x-5x=12x-4xkwadrat-xkwadrat+44
-7x=-5xkwadrat+44

d)3x(-2+x) + 3x(do kwadratu) = 6x(1+x) +15
-6x+3xkwadrat+3xkwadrat=6x+6xkwadrat+15
0=15